Antihypoxic activity of salts of (2-(5-(adamantane-1-yl)-4H-1,2,4-triazole-3-ylthio) acetate acids - V. M. Odintsova; Ye. S. Pruglo; A. S. Gotsulya; O. I. Panasenko; Ye. G. Knysh (Zaporožskij Medicinskij Žurnal)
Results of the antihypoxic activity of salts of 2-(5- (adamantane-1-yl)-4H-1,2,4-triazole-3-ylthio) acetate acid are given in the article. Promising for further studies of the biological activity of the synthesized compounds were proved.